Gender, Addiction, and Removal of Children Into Care - Russell, Lynda; Gajwani, Ruchika; Turner, Fiona; Minnis, Helen (Frontiers in Psychiatry, 2022)
Introduction – Parental addiction can result in harm to children and removal of children by the Local Authority. Less is known about the impact of removal of children on their parents and whether gender has a role in this process. Method – Data on 736 service users were obtained from the caseloads of 8 nurses and 12 social care workers from an Alcohol and Drug Recovery Service in Scotland. Gender differences in prevalence/patterns of child removal, associations between child removal and parental factors and the relationship between removal and suicidality were examined. Results – Mothers were more likely to have had one or more children removed compared to fathers (56.6% vs 17.7%; p<.001) and were more likely to have a series of individual child removals (22.5% vs 4.3%; p=.014). In addition to female gender, younger age, drug use, mental health and suicide attempts were also associated with child removal. Mothers who had children removed and women who were not mothers were more likely to have made an attempt to end their lives than women who had children but had not had them removed. Conclusion – Gender differences were apparent in prevalence and patterns of child removal. Mothers were six times more likely to have children removed compared to fathers. Child removal occurred alongside other risk factors suggesting that families need holistic support for their multiple areas of need. Services should be aware of the link between child removal and suicide and provide additional support to mothers during and after removal.